Distribution system reliability improvement using distributed generators - Jamal, Siti Hairani (2014)
Solar Energy is one of alternative source for rural electrification where no nearest grid connected available. However, since it is only depending on sun irradiation it only can feed customers need during day time only. Besides, a standalone solar energy cannot provide a continuous supply due to seasonal weather and any other periodic variations. Therefore, to satisfy the customer needs, a hybrid energy source is a better solution. A combination between solar PV with Battery and Generator set proposed as the hybrid energy source called Hybrid Distributed Generator. Investigation will be done on reliability improvement for Distribution system by using this Distributed Generator. Distributed Generator installed at Station Solar Hybrid in Tanjung Labian will be investigate. The SAIDI used as the Indices to show the reliability improvement for distribution system. SAIDI is an importance where continuity of power is high priority. Besides, SAIDI contributes the amount of time the customer is affected without power supply.